1997
DOI: 10.1080/09583159730785
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bacillus thuringiensis Berliner var. kurstaki Grown in Alternative Media

Abstract: Agro-industrial residues and by-products available in southeastern Brazil were used as ingredients for low-cost culture media for liquid fermentation of Bacillus thuringiensis var. kurstaki. Highest spore yield was obtained with a medium containing cheese whey, soya bean milk and mofasses (WSM). Crystals and spores were produced in ali media and potency o f the final product was highest for nutrient broth + yeast extract medium (N B Y). There was no correlation between the number of spores in the fermented med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
1
Order By: Relevance
“…e results indicate that it exhibits a supressive e ect at high levels, on delta-endotoxins production but improves protease activity and spores counts. In fact, Alves et al (1997) stated that the culture medium should be brought to neutral pH at harvest because high pH is optimal for Bacillus thuringiensis proteases and potentially damaging to the crystals. Furthermore, Ejiofor and Okafor (1989) concluded that low pH can restrain growth, sporulation and crystal formation of B. thuringiensis.…”
Section: Resultsmentioning
confidence: 99%
“…e results indicate that it exhibits a supressive e ect at high levels, on delta-endotoxins production but improves protease activity and spores counts. In fact, Alves et al (1997) stated that the culture medium should be brought to neutral pH at harvest because high pH is optimal for Bacillus thuringiensis proteases and potentially damaging to the crystals. Furthermore, Ejiofor and Okafor (1989) concluded that low pH can restrain growth, sporulation and crystal formation of B. thuringiensis.…”
Section: Resultsmentioning
confidence: 99%
“…This has called for a growing need to develop B. thuringiensis subsp. israelensis based products to be used in local insect control programs, as previously suggested (ALVES et al, 1997;COUCH;ROSS, 2004;MORRIS;KANAGARATNAM;CONVERSE, 1997;POOPATHI;KUMAR, 2003;PRABAKARAN;BALARAMAN, 2006;VORA;SHETHNA, 1999).…”
Section: Introductionmentioning
confidence: 80%
“…kurstaki. Highest spore yield was obtained with a medium containing cheese whey, soya bean milk and molasses (Alves et al, 1997). Other wastes, such as, sludge and broiler poultry litters were also utilized for biopesticides production (Adams et al, 2002;Vidyarthi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%